Attention to Diversity: From the Deficit Model to the Curricular Model - Arnaiz Sánchez, Pilar; Guirao Lavela, José-Manuel; Garrido Gil, Carlos F. (Education Policy Analysis Archives, 2007)
This article presents a research study developed in a Primary School (3 to 12 years) in the county of Murcia (South east of Spain). The study?s aim was to establish the educational response carried out with learners with special education needs in the school. The theoretical framework reviews the course of school integration in Spain and establishes the need to work from a curricular model. The results of this study, which follows the qualitative analysis model by Doyle (1979, 1986, 1987), show the organization structures and tasks that promote participation and integration of students with special education needs in mainstream classrooms.